2017
DOI: 10.2147/ijn.s129375
|View full text |Cite
|
Sign up to set email alerts
|

Involvement of PINK1/parkin-mediated mitophagy in ZnO nanoparticle-induced toxicity in BV-2 cells

Abstract: With the increasing application of zinc oxide nanoparticles (ZnO NPs) in biological materials, the neurotoxicity caused by these particles has raised serious concerns. However, the underlying molecular mechanisms of the toxic effect of ZnO NPs on brain cells remain unclear. Mitochondrial damage has been reported to be a factor in the toxicity of ZnO NPs. PINK1/parkin-mediated mitophagy is a newly emerging additional function of autophagy that selectively degrades impaired mitochondria. Here, a PINK… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
26
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 64 publications
(30 citation statements)
references
References 39 publications
(53 reference statements)
3
26
0
Order By: Relevance
“…Cytotoxicity observed in the glioma cells was related to increased ROS generation, and N -acetyl- l -cysteine (NAC) treatment decreased the cytotoxic effect of the ZnO NPs in these cells [123] . ZnO NP-induced cytotoxicity was also observed in microglia (BV-2 cells) exposed to 10 μg/ml ZnO NPs for 2–24 h [125] . ZnO NPs induced parkin protein translocation from the cytoplasm to the mitochondria, implying the involvement of mitophagy in ZnO NPs-induced toxicity [125] .…”
Section: Inorganic Filtersmentioning
confidence: 83%
See 2 more Smart Citations
“…Cytotoxicity observed in the glioma cells was related to increased ROS generation, and N -acetyl- l -cysteine (NAC) treatment decreased the cytotoxic effect of the ZnO NPs in these cells [123] . ZnO NP-induced cytotoxicity was also observed in microglia (BV-2 cells) exposed to 10 μg/ml ZnO NPs for 2–24 h [125] . ZnO NPs induced parkin protein translocation from the cytoplasm to the mitochondria, implying the involvement of mitophagy in ZnO NPs-induced toxicity [125] .…”
Section: Inorganic Filtersmentioning
confidence: 83%
“…ZnO NP-induced cytotoxicity was also observed in microglia (BV-2 cells) exposed to 10 μg/ml ZnO NPs for 2–24 h [125] . ZnO NPs induced parkin protein translocation from the cytoplasm to the mitochondria, implying the involvement of mitophagy in ZnO NPs-induced toxicity [125] .…”
Section: Inorganic Filtersmentioning
confidence: 83%
See 1 more Smart Citation
“…ROS might be a key mediator of inflammatory conditions, potentially stimulated by increased intracellular Ca 2+ , and further activate the NF-κB, ERK and p38 pathways, resulting in inflammation. Our previous studies also found that ZnO NPs induced oxidative damage in the brain after tongue instillation for 30 days, and ROS levels were enhanced in BV2 cells after 10 μg/mL NPs treatment [ 15 , 81 ]. Furthermore, enhanced Ca 2+ levels can lead to the activation of protein kinase C (PKC), which is involved in the activation of NF-κB and ERK [ 82 84 ].…”
Section: Discussionmentioning
confidence: 95%
“…Mitophagy is a selective autophagy process and is crucial for the maintenance of mitochondrial function in many types of cells [10]. It is well known that PQ can induce oxidative stress and produce ROS, leading to depletion of antioxidants and development of mitophagy and fibrosis [3,11,12]. Actually, previous studies have shown that PQ exposure decreased the MMP and increased PINK1 and Parkin expression, leading to mitophagy and apoptosis in A549 cells [13].…”
Section: Discussionmentioning
confidence: 99%